2018
DOI: 10.1016/j.jtho.2018.08.243
|View full text |Cite
|
Sign up to set email alerts
|

OA02.06 A Phase II Trial of Poziotinib in EGFR and HER2 exon 20 Mutant Non-Small Cell Lung Cancer (NSCLC)

Abstract: crizotinib-naive, as demonstrated by rapid and durable responses. These findings further suggest that the activity of lorlatinib differs depending on prior exposure to crizotinib. The safety profile of lorlatinib in ROS1 patients was comparable to that previously reported in the overall ALK/ROS1 population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 0 publications
0
74
0
Order By: Relevance
“…Poziotinib has been proven to be a potent inhibitor of both EGFR and HER2 exon 20 insertion mutations through preclinical models and clinical experience [78]. Its preliminary clinical activity has been reported in 2018 WCLC with confirmed ORR of 43% in advanced NSCLC [79]. Another novel agent for EGFR exon 20 insertion, TAK-788, has also been reported in 2018 WCLC [80].…”
Section: Poziotinib Tak-788 Afatinib and Pyrotinibmentioning
confidence: 99%
“…Poziotinib has been proven to be a potent inhibitor of both EGFR and HER2 exon 20 insertion mutations through preclinical models and clinical experience [78]. Its preliminary clinical activity has been reported in 2018 WCLC with confirmed ORR of 43% in advanced NSCLC [79]. Another novel agent for EGFR exon 20 insertion, TAK-788, has also been reported in 2018 WCLC [80].…”
Section: Poziotinib Tak-788 Afatinib and Pyrotinibmentioning
confidence: 99%
“…Another therapy in development, poziotinib, has also shown potential for patients with EGFR exon 20 insertions, according to findings presented at the IASLC 19th World Conference on Lung Cancer. This therapy induced a confirmed ORR of 43% among evaluable patients with EGFR exon 20 mutant NSCLC [2].…”
Section: Egfr: Uncommon Mutations-potential Targeted Treatment For Exmentioning
confidence: 74%
“…The primary results of clinical trial NCT03318939 showed that the patients with HER2 mutation are predicted to bene t from pozitinib. [10,11] Gene fusion, especially kinase gene fusion, is another uncommon mutation type in lung cancer. For example, anaplastic lymphoma kinase (ALK), ROS proto-oncogene receptor tyrosine kinase 1 (ROS1), and rearranged during transfection proto-oncogene gene (RET) are known to have fusion mutations, which account for 2-7%, 1-2%, and 1-2%of advanced NSCLC patients, respectively.…”
Section: Introductionmentioning
confidence: 99%